Beverage consumption in patients with metabolic syndrome and its association with non-alcoholic fatty liver disease: a cross-sectional study - Kositamongkol, Chayanis; Ngaohirunpat, Sorawis; Samchusri, Supawit; Chaisathaphol, Thanet; Srivanichakorn, Weerachai; Washirasaksiri, Chaiwat; Auesomwang, Chonticha; Sitasuwan, Tullaya; Tinmanee, Rungsima; Sayabovorn, Naruemit; Charatcharoenwitthaya, Phunchai; Phisalprapa, Pochamana (Frontiers in Nutrition, 2024)
Introduction: Previous research has examined the association between coffee and tea consumption and nonalcoholic fatty liver disease (NAFLD). Preclinical studies have indicated the potential hepatoprotective properties of cocoa/chocolate. However, clinical research on the consumption of cocoa/chocolate and soft drinks and their relation to NAFLD, particularly among individuals with metabolic syndrome, is limited. This study primarily aimed to assess the association between beverage consumption and NAFLD in these patients.This cross-sectional study enrolled adult patients with metabolic syndrome visited the Medicine Outpatient Department at Siriraj Hospital, Thailand, from November 2011 to January 2013. The exclusion criteria were secondary causes of hepatic steatosis, such as excessive alcohol use, viral hepatitis, or drug-induced hepatitis. Participants completed a 23item self-administered questionnaire covering their beverage consumption habits, including type, frequency, volume, duration, and additives in drinks, namely, coffee, tea, cocoa/chocolate, and soft drinks. To ensure accurate responses, these questionnaires were supplemented by face-to-face interviews. Ultrasonography was employed early in the methodology to diagnose NAFLD. Univariable analyses were used to compare the beverage consumption behaviors of participants with and without NAFLD. Multivariable logistic regression was used to adjust for potential confounders, including total beverage energy intake, age, anthropometric data, laboratory results, and comorbidities.Results: This study included 505 patients with metabolic syndrome. Of these, 341 (67.5%, 95%CI: 63.2-71.6%) were diagnosed with NAFLD. The consumption rates of coffee, cocoa/chocolate, and soft drinks were similar between the two groups. However, tea consumption was significantly more common in patients with NAFLD (68.3% vs. 51.8%, p <0.001). The groups had no significant differences in caffeine intake or total energy intake from beverages. Notably, daily intake of three or more cups of coffee was correlated with a reduced prevalence of NAFLD, with an adjusted odds ratio of 0.35 (95%CI: 0.14-0.89).This study revealed that patients with metabolic syndrome, irrespective of NAFLD status, exhibited similar patterns of beverage consumption. While no definitive associations were identified between the intake of coffee, tea, cocoa/chocolate, or soft drinks and NAFLD, a notable exception was observed. A higher consumption of coffee (≥3 cups daily) was associated with a lower prevalence of NAFLD.